2006
DOI: 10.1007/s11517-006-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostate tissue stiffness as measured with a resonance sensor system: a study on silicone and human prostate tissue in vitro

Abstract: Prostate cancer is the most common form of cancer in men in Europe and in the USA. Some prostate tumours are stiffer than the surrounding normal tissue, and it could therefore be of interest to measure prostate tissue stiffness. Resonance sensor technology based on piezoelectric resonance detects variations in tissue stiffness due to a change in the resonance frequency. An impression-controlled resonance sensor system was used to detect stiffness in silicone rubber and in human prostate tissue in vitro using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 17 publications
2
70
0
Order By: Relevance
“…Delrin is harder than most cancerous tissue, but provides a good contrast against the soft rubber for the purposes of this study. While tissue is difficult to model accurately due to its heterogeneity and variance according to location, we chose materials to represent tissue (ecoflex silicone rubber) and lumps (Delrin) which reasonably approximate an average equivalent contrast in stiffness to that found for lumps in breast [20] and prostate [17,44] tissues.…”
Section: Rubber Modelsmentioning
confidence: 99%
“…Delrin is harder than most cancerous tissue, but provides a good contrast against the soft rubber for the purposes of this study. While tissue is difficult to model accurately due to its heterogeneity and variance according to location, we chose materials to represent tissue (ecoflex silicone rubber) and lumps (Delrin) which reasonably approximate an average equivalent contrast in stiffness to that found for lumps in breast [20] and prostate [17,44] tissues.…”
Section: Rubber Modelsmentioning
confidence: 99%
“…5͒, which could be explained by the increased hardness in the cancerous tissue. 12,16 In our 21 cases ͑70 insertions͒, only 11 cases ͑38 insertions͒ that had insertions passing through both the cancerous tissue and normal tissue were included for comparison. The mean forces of all the individual insertions passing through the same type of tissues ͑tumor and normal tissue͒ in the same patients were calculated and compared.…”
Section: Iiia Insertion Force Analysismentioning
confidence: 99%
“…Some researchers analyzed prostate tissue in vitro and showed that there were variations in stiffness between tumor and normal tissue. 12 There were also variations between patients. 13 In general, tumors resulting from abnormal and excessive cell division are harder than the normal healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tactile feedback is widely used to gather other valuable tissue information, such as its stiffness, to evaluate the health of the tissue. Tumorous regions are harder than the surrounding tissue [1,2], but they cannot be visually detected; thus, tissue palpation is the only available tool to guide their localization during the procedure. In recent years, MIS surgical pro-…”
Section: Introductionmentioning
confidence: 99%